Strategi Komunikasi Antar Budaya Tentara Nasional Indonesia (TNI) di Papua - Eka Prabawa; Joni Widjayanto; Yusuf Ali; Herlina Saragih; Aris Sarjito; Siska Armawati Sufa (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2022)
Pluralism is an excellent wealth and social capital. On the other hand, pluralism has the potential for latent conflicts that can threaten security and peace in society. As one of the provinces in Indonesia that has a complex level of pluralism, Papua is inhabited by various indigenous Papuan tribes and tribes originating from outside the Papua Province. In this article, the researcher describes the communication strategy carried out by the Cenderawasih Military Command XVII and Jayapura X Lantamal. The two institutions which are the institutions of the Indonesian National Armed Forces (TNI) are responsible for creating a conducive situation in society. This research is a qualitative research. Data were collected by interview and literature study. The results of the study indicate that the application of intercultural communication strategies by the TNI as a form of its unity with the people, namely: smart-power, which consists of soft power is applied to non-armed parties, while hard power is applied to armed civilian groups. The strategy of intercultural communication is carried out with a religious, cultural, and equality approach. This research is expected to be an evaluation material for Kodam XVII Cendrawasih and Lantamal X Jayapura.